A study on trust and percieved risk towards Internet Banking Service (IBS) that influence behavioral intentions among Mirian / Dayang Khaziana Abang Khalil - Abang Khalil, Dayang Khaziana (Faculty of Business and Management, 2012)
plays an important role in many developments and it make a good product especially for banking sector. It is the easiest way to attract customer but it depends on the trust and risk that come together. Many activities could be carried out by using the internet banking services and it is convenience ways to dealing with the bank rather than using the traditional methods. Trust and perceived risks have a significant positive influence on commitment of the user. Trust can be defined as multidimensional constructs that related to the individual, cultures and contexts and perceived-risk is identified as a major barrier, discouraging consumers from considering using banking services on the internet (Black et al., 2001). Not all users understand or perceive these risks and some consumers may consider that just working with computers could be risky since online transactions involve a lack of control on the part of customers with anonymous trading partners and, consequently, the potential for opportunism. Trust towards a system is depending not only on the laws, industry regulations and contracts but also on the professionalism of the other party.